Comparative Analysis & Modeling Of Surface Roughness In Drilling - Chin, Chee Wen; Lee, Tian Soon; Subramonian, Sivarao (ITC, 2004)
Drilling is one of the basic, most frequently performed materials removing process in manufacturing industry. In spite of significant increase in the demand for economically producing holes, drill manufacturing is still considered as an esoteric art. The drilling operation is frequency used as a preliminary step for many operation like boring, reaming and tapping. Surface roughness plays an important role in product quality and manufacturing process planning.